Elevated ACE Levels Indicate Diabetic Nephropathy Progression or Companied Retina Impaired - Huang, Kangkang; Liang, Yunlai; Wang, Kun; Ma, Yating; Wu, Jiahui; Luo, Huidan; Yi, Bin (Frontiers in Clinical Diabetes and Healthcare, 2022)
Objectives Renin-angiotensin-aldosterone system plays important roles in the development of diabetic nephropathy (DN), and angiotensin converting enzyme (ACE) is the key factor in the process from angiotensin I to angiotensin II, but the variation and roles of serum ACE in DN patients are still unclear. Methods Forty-four type 2 diabetes mellitus (T2DM) patients, 75 DN patients, and 36 age-gender-matched healthy volunteers were recruited who attended Xiangya Hospital of Central South University in this case control study. Serum ACE levels and other indexes were tested with commercial kit. Results ACE levels in DN were significantly higher than T2DM and controls (F = 9.66, P < 0.001). Serum ACE levels significantly correlated with UmALB (r = 0.3650, P < 0.001), BUN (r = 0.3102, P < 0.001), HbA1c (r = 0.2046, P = 0.0221), ACR (r = 0.4187, P < 0.001), ALB (r = -0.1885, P = 0.0192), and eGFR (r = -0.3955, P < 0.001), and we got an equation that Y = 2.839 + 0.648X1 + 2.001X2 + 0.003X3 - 6.637X4 +0.416X5 - 0.134X6 (Y: ACE; X1: BUN; X2: HbA1C; X3: UmALB; X4: gender; X5: ALB; X6: eGFR, R2 = 0.655). When DN patients were divided into advanced-stage and early-stage with or without DR, ACE levels would increase when early-stage DN develops into advanced-stage or companied with DR. Conclusion Elevated serum ACE levels may hint DN progression or retina impaired of DN patients.